Metabolic Syndrome and Menopause are correlated in Moroccan women population - El Brini Otmane (EDP Sciences, 2021)
Background: Metabolic syndrome is a cluster of metabolic risk factors for type 2 diabetes mellitus and cardiovascular diseases. Physiological variations occurring in women during menopause are thought to be a predisposing factor for the metabolic syndrome. The aim of this study was to evaluate the prevalence of metabolic syndrome and its individual components according to menopausal status in a sample of Moroccan women. Methods: We analyzed data of 653 women aged 19 years and older. We used the recently published joint interim statement criteria to classify subjects as having metabolic syndrome. Results: Out of the total subjects, 262 (40.12%) were syndromic. The metabolic syndrome and abdominal obesity were more common in postmenopausal than in premenopausal women. The highest prevalence of metabolic syndrome was observed in menopausal transition especially among women aged 49-52 years (62.59%). During this period, half of women have at least three metabolic syndrome risk factors. Conclusion: Abdominal obesity associated with metabolic changes occurring in menopause was a risk factor for the development of metabolic syndrome in women. There is a need to adopt a healthy lifestyle to prevent weight gain in women. This can minimize the incidence of metabolic syndrome and its consequences as type 2 diabetes and cardiovascular diseases.